2016
DOI: 10.1002/jtr.2081
|View full text |Cite
|
Sign up to set email alerts
|

Biographical Research Methods and Their Use in the Study of Senior Tourism

Abstract: This paper explores the use of biographical research methods in the study of tourism behaviour among older adults in Freising, Germany. A qualitative biographical participatory research approach is argued to provide an emic perspective on seniors' tourism behaviour over their life course. A variety of techniques for the collection and analysis of biographical data are developed and applied including approaches to the graphical presentation of summaries of biographical data, life history guides, ecomaps and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 44 publications
(70 reference statements)
0
24
0
1
Order By: Relevance
“…In‐depth biographical interviews were conducted in two data collection phases between October 2011 and September 2012 to explore the constraints and facilitators of senior tourism behaviour (see Huber, Milne, & Hyde, ). The interviews lasted between 20 min and 3.5 hr and were conducted either in the homes of the participants or within the facilities of the senior centre.…”
Section: Methodsmentioning
confidence: 99%
“…In‐depth biographical interviews were conducted in two data collection phases between October 2011 and September 2012 to explore the constraints and facilitators of senior tourism behaviour (see Huber, Milne, & Hyde, ). The interviews lasted between 20 min and 3.5 hr and were conducted either in the homes of the participants or within the facilities of the senior centre.…”
Section: Methodsmentioning
confidence: 99%
“…They may be analyzed internally by the individuals concerned, through “self-talk” or “inner speech” ( Hurlburt et al, 2016 ; Dickens et al, 2017 ). Perceptions and memories may themselves be influenced by aging, and this applies in tourism and mobility research ( Huber et al, 2017 ; Tilley et al, 2017 ) as well as more generally ( Bradburn et al, 1987 ; Knäuper et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…These are 1) systematic study of historical archives, 2) oral histories, and 3) biography and prosopography, as both discrete and overlapping, but complementary ways of approaching hospitality and tourism studies with historical methodologies. On their own, each of the historic approaches outlined constitute a long-standing and well-developed mode of research that have been identified and used (separately) in recent hospitality and tourism research (Huber et al, 2017;Tung and Ritchie, 2011;Trapp-Fallon, 2007 andDesforges, 2000;Ladkin, 1999). However, these approaches are still not articulated in terms of how they can be used for hospitality and tourism research going forward.…”
Section: Historical Theorymentioning
confidence: 99%